Blocking GM-CSF receptor α with mavrilimumab reduces infiltrating cells, pro-inflammatory markers and neoangiogenesis in ex vivo cultured arteries from patients with giant cell arteritis. Issue 4 (19th January 2022) - Corbera-Bellalta, Marc; Alba-Rovira, Roser; Muralidharan, Sujatha; Espígol-Frigolé, Georgina; Ríos-Garcés, Roberto; Marco-Hernández, Javier; Denuc, Amanda; Kamberovic, Farah; Pérez-Galán, Patricia; Joseph, Alexandra; D'Andrea, Annalisa; Bondensgaard, Kent; et al.
Abstract : Background: Effective and safe therapies are needed for the treatment of patients with giant cell arteritis (GCA). Emerging as a key cytokine in inflammation, granulocyte-macrophage colony stimulating factor (GM-CSF) may play a role in promoting inflammation in GCA. Objectives: To investigate expression of GM-CSF and its receptor in arterial lesions from patients with GCA. To analyse activation of GM-CSF receptor-associated signalling pathways and expression of target genes. To evaluate the effects of blocking GM-CSF receptor α with mavrilimumab in ex vivo cultured arteries from patients with GCA. Methods: Quantitative real time PCR, in situ RNA hybridisation, immunohistochemistry, immunofluorescence and confocal microscopy, immunoassay, western blot and ex vivo temporal artery culture. Results: GM-CSF and GM-CSF receptor α mRNA and protein were increased in GCA lesions; enhanced JAK2/STAT5A expression/phosphorylation as well as increased expression of target genes CD83 and Spi1/PU.1 were observed. Treatment of ex vivo cultured GCA arteries with mavrilimumab resulted in decreased transcripts of CD3ε, CD20, CD14 and CD16 cell markers, and reduction of infiltrating CD16 and CD3ε cells was observed by immunofluorescence. Mavrilimumab reduced expression of molecules relevant to T cell activation (human leukocyte antigen-DR [HLA-DR]) and Th1 differentiation (interferon-γ), the pro-inflammatory cytokines: interleukin 6 (IL-6), tumour necrosis factor α (TNFα) and IL-1β, as well as molecules related to vascular injury (matrix metalloprotease 9, lipid peroxidation products and inducible nitric oxide synthase [iNOS]). Mavrilimumab reduced CD34 + cells and neoangiogenesis in GCA lesions. Conclusion: The inhibitory effects of mavrilimumab on multiple steps in the GCA pathogenesis cascade in vitro are consistent with the clinical observation of reduced GCA flares in a phase 2 trial and support its development as a therapeutic option for patients with GCA.